Local Perspectives on the Fishing and Conservation of Puntioplites bulu (Tabingalan Fish) in Kotopanjang Hydroelectric Reservoir - Fauzi Muhammad; Hendrizal Andri; Amin Bintal; Budijono (BIO Web of Conferences)
This study explores the local perspectives on fishing practices and conservation efforts related to Puntioplites bulu, locally known as “Tabingalan Fish” in the Kotopanjang Hydroelectric Reservoir. This species faces growing threats from overfishing and habitat degradation due to the reservoir’s fluctuating water levels and human activities. Using a mixedmethods approach, this research integrates surveys and semi-structured interviews with local fishermen to assess their practices, knowledge, and attitudes towards the conservation of the Tabingalan fish. The findings indicate that while the local population heavily depends on this species for their livelihoods, there is a significant gap in awareness regarding sustainable fishing practices and the importance of conservation. Traditional knowledge remains a cornerstone in the community’s fishing practices, but it often conflicts with modern conservation strategies. The study emphasizes the need for integrating local knowledge with scientific conservation efforts to enhance the effectiveness of existing programs. Challenges identified include limited access to conservation resources and the necessity for more comprehensive community engagement and educational initiatives. This research provides valuable insights for policymakers and conservationists aiming to develop more effective, community-based conservation strategies that can ensure the sustainability of Tabingalan fish while supporting local livelihoods. The study advocates for a collaborative and culturally sensitive approach to natural resource management, promoting a synergy between local communities and conservation authorities.